Triết lý nhân sinh trong tư tưởng triết học Ngô Thì Nhậm - Nguyễn, Thị Hồng Phương (Trường Đại học Đà Lạt, 2012)
Ngo Thi Nham is one of the great thinkers of the eighteenth century, he was very admired Buddhism. At the end XVIII century, at meeting many obstackles in life, right off of the hide is also the time he could easily find the similarities of Buddhism